Application of Fatty Liver Inhibition of Progression Algorithm and Steatosis, Activity, and Fibrosis Score to Assess the Impact of Non-Alcoholic Fatty Liver on Untreated Chronic Hepatitis B Patients - Huang, Yan; Gan, Qinyi; Lai, Rongtao; Wang, Weijing; Guo, Simin; Sheng, Zike; Chen, Lu; Guo, Qing; Cai, Wei; Wang, Hui; Zhao, Gangde; Cao, Zhujun; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Backgrounds & Purpose: Concurrent non-alcoholic fatty liver disease (NAFLD) in chronic hepatitis B (CHB) patients is a frequent and increasingly concerning problem because of the NAFLD pandemic. Admittedly, NAFLD can progress to non-alcoholic steatohepatitis (NASH) and severe fibrosis. Direct evidence of the fibrotic effect of NAFLD or NASH in chronic HBV infection remains lacking. We aimed to reveal the influence of concurrent histologically proven fatty liver diseases in fibrogenesis with chronic HBV infection. Methods: We performed a retrospective cross-sectional study on a liver biopsy population of CHB patients without excessive alcohol intake to evaluate the prevalence of concurrent histologically proven NAFLD or NASH according to FLIP algorithm and its association with liver fibrosis stage. Results: Among 1081 CHB patients, concurrent NAFLD was found in 404 patients (37.4%), among which, 24.0% (97/404) were NASH. The presence of NASH was an independent predictor of significant fibrosis (OR, 2.53; 95%CI, 1.52-4.21; P<0.001) and severe fibrosis (OR, 1.83; 95%CI, 1.09-3.09; P=0.023) in all patients, as well as in patients with normal ALT (predicting significant fibrosis, OR, 2.86, 95%CI, 1.34-6.10; P=0.007). Presence of lobular inflammation (P<0.001) or presence of cytological ballooning (P<0.001), rather than presence of steatosis (P=0.419), was related with severity of fibrosis in spearman correlation analysis. Conclusions: Concurrent NAFLD is common in CHB patients and NASH is an independent risk factor potentiating significant fibrosis by 2.53-fold and severe fibrosis by 1.83-fold. Besides coping with chronic HBV infection, routine assessment of co-exiting NAFLD or NASH is also important.